DETAILED CHARACTERIZATION OF CHOROIDAL MORPHOLOGIC AND VASCULAR FEATURES IN AGE-RELATED MACULAR DEGENERATION AND POLYPOIDAL CHOROIDAL VASCULOPATHY. Issue 12 (December 2017) - Gupta, Preeti; Ting, Daniel Shu Wei; Thakku, Sri GOWTHAM; Wong, Tien-Yin; Cheng, Ching-Yu; Wong, Edmund; Mathur, Ranjana; Wong, Doric; Yeo, Ian; Gemmy Cheung, Chui Ming
Abstract : Purpose: To characterize and compare morphologic and vascular features of the choroid in patients with typical age-related macular degeneration (AMD) and polypoidal choroidal vasculopathy (PCV) and to determine if PCV subtypes can be identified based on these choroidal features. Methods: Choroidal features of patients with AMD and PCV recruited from the prospectively planned Asian AMD Phenotyping Study were analyzed. Patients underwent choroidal imaging using spectral-domain optical coherence tomography with enhanced depth imaging. Raw optical coherence tomographic images were loaded on a custom-written application on MATLAB that enabled delineation for detailed morphologic and vascular analyses, including the curvature of the choroid–sclera interface, number of inflection points, choroidal thickness and choroidal vascular area within the macular (6 mm centered on fovea) and foveal (1.5 mm centered on fovea) regions. An inflection point represents the contour of the choroid–sclera interface, with >1 point signaling irregular shape. Results: A total of 156 eyes of 156 patients (78 affected eyes of 78 patients with typical AMD and 78 affected eyes of 78 patients with PCV) were analyzed. Eyes with PCV had thicker baseline choroidal thickness and greater choroidal vascular area compared with those with typical AMD ( P < 0.05); these differences were no longer significant after adjusting for age and hypertension ( P > 0.05). Typical PCV subtype with choroidal thickness of ≥257 μ m had significantly greater choroidal vascular area at macular (mean difference = 0.054 mm 2 ; P < 0.001) and foveal (mean difference = 0.199 mm 2 ; P < 0.001) regions compared with eyes with typical AMD. However, eyes with PCV without thick choroid had similar choroidal vascular area as eyes with typical AMD. Conclusion: Based on the choroidal vascular features, two subtypes of PCV can be classified: typical PCV with increased choroid vascularity and polypoidal choroidal neovascularization with low choroidal vascularity. These data provide further understanding of different AMD and PCV subtypes. Abstract : Based on the choroidal vascular features, two subtypes of polypoidal choroidal vasculopathy can be classified: typical polypoidal choroidal vasculopathy with increased choroid vascularity and polypoidal choroidal neovascularization with low choroidal vascularity. Polypoidal choroidal neovascularization, the subtype of polypoidal choroidal vasculopathy without thick choroid, has similar choroidal vascular characteristics to eyes with age-related macular degeneration, and unlike typical polypoidal choroidal vasculopathy, it does not fall within the pachychoroid spectrum.